Automatic motor activation in the executive control of action - Mcbride, Jennifer; Boy, Frédéric; Husain, Masud; Sumner, Petroc (Frontiers in Human Neuroscience, 2012)
Although executive control and automatic behaviour have been often been considered separate and distinct processes, there is strong emerging and convergent evidence that they may in fact be intricately interlinked. In this review, we draw together evidence showing that visual stimuli cause automatic and unconscious motor activation, and how this in turn has implications for executive control. We discuss object affordances, alien limb syndrome, the visual grasp reflex, subliminal priming, and subliminal triggering of attentional orienting. Consideration of these findings suggests automatic motor activation might form an intrinsic part of all behaviour, rather than being categorically different from voluntary actions.